Evaluating the Relationship between Factors Enhancing the Competitiveness of Customer Foreign Currency Services in the Banking Industry - Saeideh Rahimi; Alireza Rousta; Farzad Asayesh (تحقیقات مالی)
ObjectiveThe banking industry is one of the most important and influencing industries in today’s world and highly relies on identifying customer needs besides planning and providing solutions for proper response to their needs. Emphasis on exclusivity and strong competitive power within the banking network can significantly impact the performance and portfolios of banks. To prevent crises and future risks in banking networks, more attention should be paid to managing banks' exclusive power. Foreign currency services form a major part of banks' services and generate substantial income in both rials and foreign currencies. Therefore, the main purpose of this research is to provide a pattern for promoting the capability of competitiveness of customer foreign currency services in the banking industry. MethodsThis study is applied research in which a mixed research method has been used. Resources and articles were studied using documentary analysis. The Delphi test was applied to determine dimensions, elements, and indices. Structural equations analysis test, exploratory factor analysis, and Lisrel software were used to determine the current status and influencing elements. The statistical population in the quantitative phase comprised managers and employees engaged in banking marketing and foreign currency operations. The participants in the qualitative section consisted of experts specializing in the same field. The sample size consisted of 166 individuals, including experts and knowledgeable individuals, selected using a random sampling method. ResultsUsing the Delphi method, a pattern for promoting the capability of competitiveness of customer foreign currency services in the banking industry was extracted. The method was applied three times to reach an agreement between the experts. Moreover, the level and extreme effectiveness were confirmed using structural equations tests and exploratory factor analysis. Based on the obtained results, it can be concluded that the coefficient of all factors had a significant effect on the final model, confirming the effectiveness of each factor in promoting the competitiveness of customer foreign currency services within the banking industry. ConclusionForeign currency services constitute one the most important parts of banking services. They result in high incomes for banks, therefore, banks need to undertake requisite measures to establish a competitive edge in attracting, retaining, and servicing customers, while also evaluating the prevailing conditions in the banking sector. For each foreign currency service, banks adopt various procedures simultaneously when handling requests for foreign currency services, including submission, documentation completion, and customer file creation. Banks can possess a greater share of the foreign currency market by adopting proper strategies and determining elements for the capability of competitiveness. This study shows that major elements such as “banking activity”, “credit portfolio”, “monetary and financial”, “market share” and “extra-organizational” shape patterns for promoting the capability of competitiveness of customers’ foreign currency services in the banking industry.